Pengembangan Keterampilan SDM di Kelurahan untuk Mendukung Pemberdayaan Masyarakat Berbasis Teknologi - Eko Sudarso; Raden Roro ayu Metarini; Andri Priadi (Universitas Pamulang, 2025)
Human resource development (HRD) at the urban village (kelurahan) level is one of the keystrategies in promoting sustainable community empowerment. This community service activity aimsto enhance the capacity and skills of human resources in Pamulang Barat through training andmentoring based on information and communication technology. The methods used include needsassessment, development of training modules, implementation of basic technology workshops (suchas the use of digital applications, local e-commerce platforms, and social media for promotingmicro, small, and medium enterprises), and evaluation of training outcomes. The results of theactivity indicate an increase in participants’ understanding and ability to access and utilizetechnology to support economic and social activities in their communities. Furthermore, thisprogram has fostered the formation of digital community groups that act as agents of change at thekelurahan level. Therefore, this program makes a tangible contribution to strengthening inclusiveand sustainable technology-based community empowerment